“Existe diferença na evolução de pacientes transplantados renais com ou sem cirurgia de banca?” - SILVA, Rafaelle Taynah Soares da (2019)
The number of people who need renal transplantation is greater than the amount of available organs. The bench, or backtable, surgery under hypothermia appeared as the possibility of vascular correction and use of the kidneys with variation of vascular pedicle anatomy, previously considered unviable for transplantation. Comparative studies among patients submitted to the bench surgery procedure for reconstruction of the vascular pedicle on renal transplantation and patients without anomaly of this structure are rare, mainly regarding the functionality of the new organ in long period of time, being relevant to attest the success of this technique. The objective of the research is evaluate the evolution of kidney transplanted patients undertaken to bench surgery, testifying its effectiveness and establishing comparison with the surgeries without renal pedicle reconstruction regarding the organ functionality through the analysis of the glomerular filtration rate. The study was observational analytical of retrospective cohort, with 172 people out of 422 patients submitted to renal transplantation at Ophir Loyola Hospital between 2005 and 2016, separated into two groups, A and B. Group A has 90 patients undergoing to kidney transplantation who required bench surgery. Control group B is composed of 82 patients undergoing to kidney transplantation without bench surgery need. Demographic aspects data were charted, beyond the estimate of glomerular filtration rate through the developed formula at the Modification of Diet in Renal Disease (MDRD) study, reduced version and the equation of Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI). Among the patients submitted to renal transplantation, at HOL, the majority was male, between 21 and 50 years old and the most prevalent race was brown. The number of bench surgeries realized in the research period was nearly 21,3% of the total number of transplants performed between 2005 and 2016. Regarding the type of donor, most were cadavers. About the studied sample submitted to the bench surgery, most had vascular anomaly of the arterial type, being the double renal artery (28,6%) the most frequent pedicle anomaly. No statistical relevance was found by comparing the renal function of kidney transplanted patients by bench surgery and those who didn’t undergo bench surgery with 1 year, 5 years, 10 years or more after transplantation. In this study, no difference was observed, in a long period of time, on the renal function after renal transplantation on patients that required renal pedicle reconstruction, when compared to those who didn’t need it.